2012
DOI: 10.1002/etc.1875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of test design and temperature in a partial life‐cycle study with the freshwater gastropod Potamopyrgus antipodarum

Abstract: Potamopyrgus antipodarum is a candidate for a standardized mollusk partial life-cycle study. This is a comparative study of two test designs (microplate and beaker), with additional endpoints to the proposed guideline methods, for example, tracking of continuous reproductive output over 28 d and attributing it to individual female snails. In addition, an investigation of the effects of temperature (16, 20, and 25°C) on reproduction was also conducted employing the microplate design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…Here, we report a strong seasonal variability in neonate production and growth rates. Several studies have shown that P. antipodarum life‐history traits are strongly correlated with water temperature . The quality of the fits observed in Figure confirms this pattern.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, we report a strong seasonal variability in neonate production and growth rates. Several studies have shown that P. antipodarum life‐history traits are strongly correlated with water temperature . The quality of the fits observed in Figure confirms this pattern.…”
Section: Discussionsupporting
confidence: 77%
“…In situ caging experiments were conducted from October 2009 to November 2010 during 10 campaigns lasting 21 d. We measured contrasted environmental conditions between the different campaigns. In this way, mean water temperature, which is known to strongly influence P. antipodarum life‐history traits , varied from 4.6 °C to 22.7 °C. We focused our experiments on measuring fertility and growth.…”
Section: Methodsmentioning
confidence: 99%
“…In general, estimates of reproduction for P. antipodarum vary widely among studies, and the high variation may be related to differences in experimental design (e.g., light:dark cycle, food quality, etc.). For instance, reproduction in P. antipodarum has been found to be strongly correlated with temperature, with increased reproduction at 16 °C compared with that at 7 °C and 8 °C and compared with that at 24 °C and 25 °C , and furthermore at 20 °C compared with that at 16 °C and 25 °C . In addition, it has been shown that the reproductive cycle of P. antipodarum changes with seasons, both in the field and in the laboratory .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study emphasizes the importance of appropriate test durations, especially for the investigation of sublethal effects. Although Macken et al , for example, demonstrated that significant differences in the reproduction can occur after 28 d, the impact of SOT would not have been observed within this time period. Therefore, our results support the recommended test duration of 8 wk for the establishment of a standard chronic ecotoxicological test with the New Zealand mudsnail P. antipodarum .…”
Section: Discussionmentioning
confidence: 91%